1996
DOI: 10.21273/jashs.121.4.730
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Browning of Rambutan is a Consequence of Water Loss

Abstract: Rambutan (Nephelium lappaceum L.) rapidly lose their attractive appearance after harvest due to a superficial pericarp browning. Storage at high humidity minimizes fruit desiccation and may, therefore, delay browning onset. This paper examines the effect of reduced water loss rate on browning that may occur with time. Rambutan fruit pericarp browning beyond a commercially saleable level occurred at a weight loss of 25% to 40%. This depended on duration and storage relative hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 7 publications
(9 reference statements)
0
5
0
3
Order By: Relevance
“…Durante os 70 dias de armazenamento, as uvas não tiveram variações significativas no teor de fenóis, cuja média foi 0,332% (Tabela 1). Esta resposta pode ser favorável ao prolongamento da conservação pós-colheita da uva 'Itália' uma vez que, de acordo com Landrigan et al (1996), o escurecimento da casca decorrente da perda de água do fruto após a colheita aumenta com o decréscimo no nível de fenóis.…”
Section: Resultsunclassified
“…Durante os 70 dias de armazenamento, as uvas não tiveram variações significativas no teor de fenóis, cuja média foi 0,332% (Tabela 1). Esta resposta pode ser favorável ao prolongamento da conservação pós-colheita da uva 'Itália' uma vez que, de acordo com Landrigan et al (1996), o escurecimento da casca decorrente da perda de água do fruto após a colheita aumenta com o decréscimo no nível de fenóis.…”
Section: Resultsunclassified
“…The rapid desiccation of the spinterns may be related to the high surface : volume ratio and the poor closing capability of stomata (Landrigan et al, 1994). Various studies have suggested that reducing weight loss from desiccation is crucial in preventing browning (Landrigan et al, 1996a(Landrigan et al, , 1996bPaull et al, 1995). Desiccation can be reduced by storage at low temperatures and high relative humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological browning may be caused by degradation of anthocyanin pigments from increased polyphenol oxidase, as in litchi (Underhill and Critchley, 1992), or by oxidation of phenols to quinones that polymerize to form brown pigments (Mayer and Harel, 1979). Mechanical damage, such as bending of spinterns, can hasten desiccation and browning in fruits (Landrigan et al, 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…Los frutos pesaron en promedio 36,4 g, los tamaños fueron superiores a los reportados por otros autores que reportaron 32,0 g para cultivos en Costa Rica (Vargas, 2003) hasta 24,0 g para condiciones de Veracruz en México (Del Ángel et al, 2014). Los grados Brix fueron elevados con un promedio del 19,6% teniendo en cuenta que la concentración de sólidos solubles totales que debe tener un fruto de calidad comercial está entre el 16-18% (Landrigan et al, 1996).…”
Section: Calidad De Frutounclassified